Comparative Analysis of Selected Elements of Polish and Spanish Accounting System - Burchart, Renata; Monteys, Ramon Soldevila de (Olsztyn Economic Journal, 2013)
The article presents the history and premises of revolts of accounting and basic rules of double-entry bookkeeping system, which is international, so is the same both in Poland and Spain. The comparative analysis verifies, the existence of many similarities and only a few differences between Polish and Spanish annual accounts. Differences in both countries between a structure of balance sheet and income statement are of a minor character. There are different economic conditions for firms in both countries which can prepare the abbreviated format for annual accounts. The analysis of documents shows that Spanish General Accounting Plan is much more precise (359 pages) then Polish Act of Accounting (137 pages).